Application of Cmc as Thickener on Nanoemulsions Based on Olive Oil: Physical Properties and Stability - Arancibia-Aguilar, C; Navarro-Lisboa, R; Matiacevich, S (Hindawi Limited, 2016)
Carboxymethyl cellulose (CMC) is a hydrocolloid with surface activity that could act as emulsifiers in oil-in-water emulsions; however the principal role is that it acts as structuring, thickening, or gelling agent in the aqueous phase. This study aims to evaluate the application of CMC as thickener into nanoemulsions based on olive oil and their influence on particle characteristics, flow behavior, and color. Four nanoemulsions with different oil (5% and 15% w/w olive oil) and CMC (0.5% and 0.75% w/w) concentration and two control samples without CMC added were prepared using Tween 80 as emulsifier. All physical properties studied on nanoemulsions were depending on both oil and CMC concentration. In general, z-average particle size varied among 107-121 nm and those samples with 5% oil and CMC were the most polydisperse. The addition of CMC increased anionic charge of nanoemulsions obtaining zeta potential values among -41 and -55 mV. The oil concentration increased both consistency and pseudoplasticity of samples, although samples were more stable to gravitational separation at the highest CMC concentration. Color of nanoemulsions was affected principally by the oil concentration. Finally, the results showed that CMC could be applied in nanoemulsions as thickener increasing their physical stability although modifying their physical properties. © 2016 C. Arancibia et al.